2018
DOI: 10.1245/s10434-018-6397-6
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Mediastinoscopy Increases the Risk of Postoperative Pneumonia After Pulmonary Lobectomy

Abstract: Mediastinoscopy may be associated with an increased risk of POP after pulmonary lobectomy. This observation should be examined in other datasets as it potentially impacts preresectional staging algorithms for patients with lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
3
5
0
Order By: Relevance
“…The present study showed that male sex, longer surgery duration, higher leukocyte count, larger intraoperative use of colloid, and intraoperative use of hormones were significantly associated with a higher rate of developing postoperative pneumonia especially among elder patients with lung cancer after video-assisted thoracoscopic surgery. Of the five significant variables identified by the LASSO method, two of them, i.e., male sex and longer surgery duration, were previously confirmed by other studies ( 22 , 25 , 26 , 33 ). Since smoking status and history of COPD were previously confirmed to be significant with postoperative pneumonia ( 14 , 22 , 26 , 27 , 31 ), we also added the both to the algorithm.…”
Section: Discussionsupporting
confidence: 70%
“…The present study showed that male sex, longer surgery duration, higher leukocyte count, larger intraoperative use of colloid, and intraoperative use of hormones were significantly associated with a higher rate of developing postoperative pneumonia especially among elder patients with lung cancer after video-assisted thoracoscopic surgery. Of the five significant variables identified by the LASSO method, two of them, i.e., male sex and longer surgery duration, were previously confirmed by other studies ( 22 , 25 , 26 , 33 ). Since smoking status and history of COPD were previously confirmed to be significant with postoperative pneumonia ( 14 , 22 , 26 , 27 , 31 ), we also added the both to the algorithm.…”
Section: Discussionsupporting
confidence: 70%
“…Meanwhile, more details of variables on patient demographics and characteristics should be included in this study. Clarification regarding the abovementioned omissions would greatly solidify the conclusions of the study by Yendamuri et al 1 DISCLOSURE Jiong-Jie Yu, Ju-Dong Li, and Tian Yang have no conflicts of interest to declare.…”
mentioning
confidence: 57%
“…We read with great interest the article by Yendamuri et al 1 This retrospective study identified that mediastinoscopy may be associated with an increased risk of postoperative pneumonia after pulmonary lobectomy for patients with lung cancer. Herein, we would like to raise the following comments.…”
mentioning
confidence: 99%
“…Yu, Li, and Yang for their comments on our recent publication. 1 Although already stated in the manuscript, we would like to reiterate that we do recognize that the comparison groups have differences between them, hence multivariable analyses have been performed and presented. The additional benefit of a propensity scorematched analysis is questionable.…”
mentioning
confidence: 99%
“…Covariates included in the model depended on the dataset and are found in Tables 1 and 4 of the original article. 1 Based on the approach outlined by Stürmer et al, 3 the propensity scores were then trimmed and inverse probability weights (IPW) were calculated. A weighted logistic regression model, weighted by the IPW, was then used to estimate the effect of concomitant mediastinoscopy on the risk of postoperative pneumonia.…”
mentioning
confidence: 99%